Indian 2000 : The next fifteen years - Roach James, R.(ed.) (New Delhi, 1986)
The essays in this volume were written for a seminar at The University of Texas at Austin, February 7-9, 1985. Originally planned as a small local enterprise, the seminar was enlarged by its inclusion as an event of the 1985-86 Festival of India in the United States. We are grateful for the assistance of the Indo-US Sub commission on Education and Culture, especially Maureen Libel of the Sub commission's New York office, and for contributions in kind by Air India and Pan American World Airways.
The papers of a symposium conducted by the Center for Asian Studies of the University of Texas at Austin as part of the 1985-86 Festival of India in the United States.
Keywords: Social change-India